An association analysis of sow parity, live-weight and back-fat depth as indicators of sow productivity. (18th July 2018) - Lavery, A.; Lawlor, P. G.; Magowan, E.; Miller, H. M.; O'Driscoll, K.; Berry, D. P.
Abstract : Understanding how critical sow live-weight and back-fat depth during gestation are in ensuring optimum sow productivity is important. The objective of this study was to quantify the association between sow parity, live-weight and back-fat depth during gestation with subsequent sow reproductive performance. Records of 1058 sows and 13 827 piglets from 10 trials on two research farms between the years 2005 and 2015 were analysed. Sows ranged from parity 1 to 6 with the number of sows per parity distributed as follows: 232, 277, 180, 131, 132 and 106, respectively. Variables that were analysed included total born (TB), born alive (BA), piglet birth weight (BtWT), pre-weaning mortality (PWM), piglet wean weight (WnWT), number of piglets weaned (Wn), wean to service interval (WSI), piglets born alive in subsequent farrowing and sow lactation feed intake. Calculated variables included the within-litter CV in birth weight (LtV), pre-weaning growth rate per litter (PWG), total litter gain (TLG), lactation efficiency and litter size reared after cross-fostering. Data were analysed using linear mixed models accounting for covariance among records. Third and fourth parity sows had more ( P <0.05) TB, BA and heavier BtWT compared with gilts and parity 6 sow contemporaries. Parities 2 and 3 sows weaned more ( P <0.05) piglets than older sows. These piglets had heavier ( P <0.05) birth weights than those from gilt litters. LtV and PWM were greater ( P <0.01) in litters born to parity 5 sows than those born to younger sows. Sow live-weight and back-fat depth at service, days 25 and 50 of gestation were not associated with TB, BA, BtWT, LtV, PWG, WnWT or lactation efficiency ( P >0.05). Heavier sow live-weight throughout gestation was associated with an increase in PWM ( P <0.01) and reduced Wn and lactation feed intake ( P <0.05). Deeper back-fat in late gestation was associated with fewer ( P <0.05) BA but heavier ( P <0.05) BtWT, whereas deeper back-fat depth throughout gestation was associated with reduced ( P <0.01) lactation feed intake. Sow back-fat depth was not associated with LtV, PWG, TLG, WSI or piglets born alive in subsequent farrowing ( P >0.05). In conclusion, this study showed that sow parity, live-weight and back-fat depth can be used as indicators of reproductive performance. In addition, this study also provides validation for future development of a benchmarking tool to monitor and improve the productivity of modern sow herd.